Possibility of municipal waste management with Refuse-Derived Fuel (RDF) mixed paper and garden in Depok City - Eva Nur Fauziah; Mega Mutiara Sari; I Wayan Koko Suryawan (Universitas Pakuan, 2023)
Paper and garden waste are among the various types of rubbish commonly encountered in urban areas in Indonesia, including the city of Depok. Notably, not all paper waste can be recycled by garbage collectors into new products. In addition, garden waste is also garbage, one of the wastes produced daily from gardening activities. This study analyzed the potential for reducing paper and garden waste using as Refuse-Derived Fuel or RDF in Depok City. This study analyzes the quality of RDF based on the parameters of water content, ash content, density, and calorific value resulting from the material substitution. The results were analyzed using the multicollinearity and Kepner-Tregoe Decision Analysis (KTDA). The results of the multicollinearity test showed that the ash and water content could reduce the calorific value of RDF mixed with paper and garden waste. The addition of garden waste composition can increase the calorific value. Based on the results of decision analysis using KTDA, it shows that the variation of the mixture of 75% paper waste and 25% wood waste has the most prominent points compared to other variations. Material Flow Analysis (MFA) utilization of this waste can reduce the generation of paper and garden waste by 3.5% and 12.3%, respectively.Sampah kertas dan kebun adalah beberapa jenis sampah yang biasa ditemukan di perkotaan di Indonesia, termasuk kota Depok. Perlu dicatat, tidak semua sampah kertas dapat didaur ulang oleh pemulung menjadi produk baru. Selain itu, sampah kebun juga merupakan salah satu sampah yang dihasilkan sehari-hari dari kegiatan berkebun. Kajian ini menganalisis potensi pengurangan sampah kertas dan kebun dengan menggunakan Refuse-Derived Fuel atau RDF di Kota Depok. Penelitian ini menganalisis kualitas RDF berdasarkan parameter kadar air, kadar abu, berat jenis, dan nilai kalor hasil substitusi bahan. Hasil penelitian dianalisis menggunakan multikolinearitas dan Analisis Keputusan Kepner-Tregoe (KTDA). Hasil uji multikolinearitas menunjukkan bahwa kadar abu dan air dapat menurunkan nilai kalor RDF yang bercampur dengan kertas dan sampah kebun. Penambahan komposisi sampah kebun dapat meningkatkan nilai kalor. Berdasarkan hasil analisis keputusan menggunakan KTDA menunjukkan bahwa variasi campuran 75% limbah kertas dan 25% limbah kayu memiliki poin paling menonjol dibandingkan variasi lainnya. Pemanfaatan Material Flow Analysis (MFA) limbah ini dapat mengurangi timbulan limbah kertas dan kebun masing-masing sebesar 3,5% dan 12,3%.